Analisis Kandungan Bahan Kimia Obat Allopurinol Dalam Jamu Asam Urat Yang Beredar Di Kota Batam Secara Kromatografi Lapis Tipis - Aprilya Sri Rachmayanti (Centre of Applied Science for Pharmaceutical Science Universitas Jenderal Soedirman, 2025)
The high public interest in herbal medicines, particularly those used to relieve joint pain and gout, has encouraged some manufacturers to enhance product efficacy to achieve rapid therapeutic effects. One type of pharmaceutical adulterant (Bahan Kimia Obat, BKO) that is potentially added to herbal medicines is allopurinol. This study aimed to determine whether gout herbal medicines circulating in Batam City contain pharmaceutical adulterants and to analyze allopurinol using thin-layer chromatography (TLC). Six brands of gout herbal medicines marketed in Batam City were used as samples. Identification of allopurinol was performed using the TLC method, indicated by the appearance of purple spots under ultraviolet light at 254 nm. The mobile phase used consisted of n-butanol (C₄H₁₀O) and ammonium hydroxide (NH₄OH), while ammonium hydroxide (NH₄OH) and sodium hydroxide (NaOH) were used as solvents, and silica gel GF254 plates were employed as the stationary phase. The TLC analysis showed that none of the gout herbal medicine samples contained allopurinol, as no sample spots exhibited retention factor (Rf) values equal to or close to those of the allopurinol standard under UV 254 nm observation. Therefore, quantitative analysis was not continued because all six samples yielded negative results for allopurinol.